The Role of Electronic Payment Systems in Improving Monetary Efficiency in Indonesia - Roy Andi Saputra Hia; Lia Nazliana Nasution; Dewi Mahrani Rangkuty (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the effect of e-wallets, QRIS, and mobile banking on the inflation rate in Indonesia. The research adopts a quantitative approach with a causal associative design to examine the relationships among variables. The data used in this study consist of transaction volume data for e-wallets, QRIS, and mobile banking, as well as Consumer Price Index (CPI) data for the period January 2021 to October 2025. The data were analyzed using multiple linear regression techniques. The results indicate that: (1) e-wallets (X1) have a significant effect on the inflation rate (Y); (2) QRIS (X2) also has a significant effect on the inflation rate (Y); (3) mobile banking (X3) has a significant effect on the inflation rate (Y); and (4) simultaneously, e-wallets, QRIS, and mobile banking have a significant effect on the inflation rate in Indonesia, contributing 49.1% to the variance, while the remaining 50.9% is influenced by other factors beyond the scope of this study. These findings suggest that the development of digital payment systems is significantly associated with inflation dynamics in Indonesia. Therefore, digital payment systems can be viewed as one of the supporting instruments in maintaining price stability and enhancing monetary efficiency.